Enhanced Catalytic Glycerol Oxidation Activity Enabled by Activated‐Carbon‐Supported Palladium Catalysts Prepared through Atomic Layer Deposition. Issue 5 (18th January 2018) - Weber, Matthieu; Collot, Philippe; El Gaddari, Hoda; Tingry, Sophie; Bechelany, Mikhael; Holade, Yaovi
Abstract: The ability to precisely engineer advanced catalysts for the oxygen reduction reaction (ORR) and glycerol oxidation reaction (GOR) is crucial for the deployment of fuel cells (FCs) and electrolyzers. In this work, we used an atomic layer deposition (ALD) process to prepare highly dispersed palladium nanoparticles (PdNPs) on electro‐activated carbon felt electrodes. The prepared PdNPs were well dispersed and presented diameters of 4–6 nm, corresponding to a mass loading of 96 μgPd  cm −2 or 0.9 wt.%. For the GOR, the as‐synthesized nanocatalysts outperformed the commercial Pd/C (20 wt.%) reference by an order of magnitude. The bare electrode also displays distinguished kinetics towards the ORR. The enhanced performance is explained by the good palladium‐carbon interaction and the reduced aggregation and/or detachment of PdNPs. The results uncovered herein provide new strategic routes for the development of advanced electrodes for applications in electrochemical energy conversion. Abstract : Go further : The direct growth of metallic nanoparticles onto usable electrodes is a remarkable opportunity to fabricate advanced electrocatalysts. Herein, tightly optimized atomic layer deposition onto electrodes enables the fabrication of a highly active and multifunctional Pd nanocatalyst. This work provides a rational strategy for a precise engineering of materials at the atomic scale for a simultaneous decrease of metal loading and increase in electrode performance.